Preparation method and application of double-defect Mg-MOF derivative metal oxide

By using double-deficient Mg-MOF derived metal oxide to prepare nanomagnesium oxide, the problem of low phosphorus adsorption capacity of existing phosphorus adsorbents is solved, and efficient recycling of phosphate in wastewater is achieved, and the application promotion value is high.

CN119869479APending Publication Date: 2025-04-25AGRO ENVIRONMENTAL PROTECTION INST OF MIN OF AGRI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510200707.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing phosphorus adsorption capacity of phosphorus adsorbents is low, making it difficult to effectively recover phosphate in livestock and poultry farming wastewater, resulting in eutrophication of water bodies and ecosystem damage.

Method used

The double-deficient Mg-MOF derived metal oxide was calcined by the Mg-MOF sacrificial template method to generate nanomagnesium oxide, which had high concentrations of oxygen defects and magnesium defects, and formed slit-type elongated holes, which improved the adsorption capacity of phosphate.

Benefits of technology

The efficient recovery of phosphate in wastewater was achieved, with an adsorption amount greater than 300mg P/g, which was much higher than existing materials such as biochar, LDH, perovskite, and in actual aquaculture wastewater, when the dosage amount is 1.2g/L, the phosphate removal rate reached 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869479A_ABST
    Figure CN119869479A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a double-defect Mg-MOF derivative metal oxide, and the preparation method comprises the following steps: dissolving DHTA, H3BTC or AA and MgNO3. 6H2O in DMF, EtOH and deionized water to form a mixed solution; carrying out high-temperature treatment on the mixed solution, collecting crystals, and washing for later use; and calcining the crystals at a high temperature to obtain a nano metal oxide which has oxygen defects and magnesium defects and is used for adsorbing and removing phosphate in wastewater. Nano magnesium oxide is generated through calcination by adopting an Mg-MOF sacrificial template method, meanwhile, high-concentration oxygen defects and high-concentration magnesium defects are achieved, particularly, nano metal oxide prepared by adopting AA further forms slit-type long and thin holes to expose more binding sites, and through the adsorption mechanism of ligand exchange, inner sphere complexing and electrostatic attraction, the nano magnesium oxide can be used for preparing the nano magnesium oxide with the high-concentration oxygen defects and the high-concentration magnesium defects. And the adsorption capacity is far higher than the adsorption capacity of the existing adsorbent on the phosphate, so that the adsorbent has practical application potential and relatively high application and popularization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phosphorus-containing wastewater treatment, and in particular to a preparation method and application of a double-defect Mg-MOF derived metal oxide. Background Art

[0002] Phosphorus concentrations exceeding 0.02 mg / L are considered to have reached the eutrophication standard for water bodies, leading to damage to water quality and natural ecosystems. Livestock and poultry farming is the industry with the most serious phosphorus pollution. Animal feces, urine, feed residues and pen flushing water all carry a large amount of phosphorus. The "Second National Pollution Source Census Bulletin" shows that the total phosphorus discharged through livestock and poultry wastewater is as high as 119,700 tons per year, accounting for 37.95% of the national sewage TP discharge, which is 15.15 times and 1.25 times the total phosphorus discharge from industrial and domestic sources. Phosphorus pollution in livestock and poultry farming has become an important factor restricting the sustainable development of China's agriculture. Phosphorus removal is of great significance to curbing agricultural non-point source pollution and improving China's water environment quality.

[0003] Among the many phosphorus recovery methods, the adsorption method is eye-catching because of its simple material preparation, low cost, few by-products, no energy consumption, and environmental friendliness. The choice of adsorbent plays a decisive role in the adsorption performance. Currently, phosphorus adsorbents such as biochar, LDH, and perovskite have been developed, and the overall adsorption capacity is 50-200 mg P / g, which needs to be further improved. Therefore, the research and development of an adsorption material that can improve the phosphorus adsorption capacity and enhance the phosphorus recovery ability has become a technical direction that technicians in this field need to solve urgently. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a preparation method and use of a double-defect Mg-MOF-derived metal oxide.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a double-defect Mg-MOF-derived metal oxide comprises the following steps:

[0007] S1. Dissolving DHTA, H3BTC or AA and a magnesium metal salt in DMF, EtOH and deionized water to form a mixed solution, wherein the magnesium metal salt is MgNO3·6H2O or MgCl3·H2O;

[0008] S2. The mixed solution is treated at high temperature and the crystals are collected and washed for later use;

[0009] S3. calcining the washed crystals at high temperature to obtain nano metal oxides.

[0010] Among them, DHTA is 2,5-dihydroxyterephthalic acid, H3BTC is 1,3,5-benzenetricarboxylic acid, AA is adipic acid, DMF is N`N-dimethylformamide, and EtOH is anhydrous ethanol.

[0011] According to the above technical solution, preferably, in step S1, DHTA, H3BTC or AA and MgNO3·6H2O in a ratio of 1:3-1:4 are dissolved in 60mL DMF, 4mL EtOH and 4mL deionized water, and ultrasonically treated for 1-2h to form a mixed solution. Specifically, 3mmol DHTA, H3BTC or AA and 10mmol MgNO3·6H2O can be dissolved in 60mL DMF, 4mL EtOH and 4mL deionized water, and ultrasonically treated for 2h to form a mixed solution.

[0012] According to the above technical solution, preferably, step S2 includes:

[0013] The mixed solution is heated in an oven at 120-180° C. for 12-48 hours, and the crystals are collected after cooling overnight;

[0014] The product was washed twice with 50 mL of DMF and EtOH respectively, and dried at 80° C. for 8 h.

[0015] Specifically, the mixed solution can be transferred to a polytetrafluoroethylene-lined high-pressure reactor with a volume of 100 mL, heated in an oven at 120° C. for 24 h, and the crystals are collected after cooling; washed twice with 50 mL of DMF and EtOH respectively, and dried in a vacuum drying oven at 80° C. for 8 h.

[0016] According to the above technical solution, preferably, in step S3, the washed crystals are heated to 600° C. at a heating rate of 5° C. / min in a muffle furnace and calcined in an air atmosphere for 8 hours to obtain the nano metal oxide.

[0017] According to the above technical solution, preferably, in step S1, AA and MgNO3·6H2O are dissolved in DMF, EtOH and deionized water to form a mixed solution.

[0018] The present application also discloses a use of a double-defect Mg-MOF-derived metal oxide. Based on the preparation method of the above-mentioned double-defect Mg-MOF-derived metal oxide, the nano metal oxide has both oxygen defects and magnesium defects, and is used for adsorbing and removing phosphates in wastewater.

[0019] According to the above technical solution, preferably, the nano metal oxide prepared by AA has oxygen defects and magnesium defects, and also forms slit-shaped elongated holes to expose more binding sites for adsorbing and removing phosphates in wastewater.

[0020] According to the above technical solution, preferably, the nano metal oxide prepared by using AA has an adsorption capacity of more than 300 mg P / g for phosphate in wastewater under the environment of pH=8.

[0021] According to the above technical solution, preferably, the nano metal oxide prepared by AA is applied to aquaculture wastewater with a concentration of 40 mg P / L, and the phosphate removal rate is 100% after the addition amount is 1.2 g / L.

[0022] The beneficial effects of the present invention are:

[0023] The present invention adopts the Mg-MOF sacrificial template method to calcine and generate nano magnesium oxide with different morphologies, pore structures and defect concentrations, and has high concentrations of oxygen defects and magnesium defects. In particular, the nano metal oxide prepared by AA also forms slit-shaped elongated holes to expose more binding sites, and removes phosphates in wastewater through the adsorption mechanism of ligand exchange, inner sphere complexation and electrostatic attraction, thereby achieving the purpose of efficient recovery of phosphates.

[0024] At the same time, the defect-rich nanomagnesium oxide was prepared by the Mg-MOF sacrificial template method, and the adsorption capacity of phosphate in wastewater can be greater than 300mg P / g, which is much higher than the adsorption capacity of phosphate by current biochar, LDH, perovskite and other phosphorus adsorption materials (the adsorption capacity is generally 50-200mg P / g). In addition, in actual aquaculture wastewater, when the AA-MgO dosage is 1.2g / L, the phosphate removal rate reaches 100%, indicating that it has the potential for practical application and has a high application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 These are the SEM and TEM spectra of DHTA-MgO, H3BTC-MgO and AA-MgO in the present invention, wherein a and b are SEM images of DHTA-MgO, c and d are TEM and IFFT images of DHTA-MgO, e and f are SEM images of H3BTC-MgO, g and h are TEM and IFFT images of H3BTC-MgO, i and j are SEM images of AA-MgO, and k and l are TEM and IFFT images of AA-MgO.

[0026] Figure 2 It is a schematic diagram of the physical properties of nano-MgO derived from different Mg-MOF precursors in the present invention.

[0027] Figure 3 It is the XPS spectrum of material elements of DHTA-MgO, H3BTC-MgO and AA-MgO in the present invention.

[0028] Figure 4It is the XPS spectrum of O1s in DHTA-MgO, H3BTC-MgO and AA-MgO of the present invention.

[0029] Figure 5 It is the XPS spectrum of Mg 1s in DHTA-MgO, H3BTC-MgO and AA-MgO of the present invention.

[0030] Figure 6 These are the defect types and concentrations detected by EPR of DHTA-MgO, H3BTC-MgO and AA-MgO in the present invention.

[0031] Figure 7 It is a schematic diagram of the phosphate adsorption performance of DHTA-MgO, H3BTC-MgO and AA-MgO in the present invention, wherein a is an adsorption isotherm model, b is an adsorption kinetic model (T=25°C, V=50mL, dosage=0.02g, pH=7), c is a schematic diagram of the effect of the initial pH value of the solution on the phosphate adsorption performance, d is the Zeta potential of AA-MgO, e is a schematic diagram of the effect of the adsorbent dosage on the phosphate adsorption performance, g is a schematic diagram of the effect of coexisting cations and humic acid (C0=160mg P / L, T=25°C, V=50mL, dosage=0.02g) on ​​the phosphate adsorption performance, and h is a schematic diagram of the AA-MgO dosage on the phosphorus adsorption verification experiment in dairy cattle breeding wastewater.

[0032] Figure 8 It is the fitting parameter of the adsorption isotherm model of DHTA-MgO, H3BTC-MgO and AA-MgO in the present invention.

[0033] Fig. 9 It is the fitting parameter of the adsorption kinetic model of DHTA-MgO, H3BTC-MgO and AA-MgO in the present invention.

[0034] Fig.10 These are SEM images of DHTA-MgO, H3BTC-MgO and AA-MgO in the present invention after adsorbing phosphate, wherein a is the SEM image of DHTA-MgO, b is the SEM image of H3BTC-MgO, and c is the SEM image of AA-MgO.

[0035] Fig.11 It is the XPS spectrum of AA-MgO in the present invention before and after adsorbing phosphate, wherein a is the XPS spectrum of AA-MgO material elements, b is the XPS spectrum of P 2p, c is the XPS spectrum of Mg 1s, and d is the XPS spectrum of O1s.

[0036] Fig.12It is a structural model of AA-MgO (111) before and after the adsorption of phosphate in the present invention and a schematic diagram of the spin polarization density of states (DOS), wherein a, c, and e respectively represent the perfect crystal plane, oxygen vacancy crystal plane, and magnesium vacancy crystal plane of the AA-MgO (111) structural model, and b, d, and f respectively represent the perfect crystal plane, oxygen vacancy crystal plane, and magnesium vacancy crystal plane of the DOS of AA-MgO (111).

[0037] Fig.13 It is a schematic diagram of the phosphorus removal mechanism of AA-MgO water in the present invention. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiment. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the invention.

[0039] MOFs are a type of crystalline porous material with a periodic network structure, strong adsorption capacity and high targeting. MOF-based derivative materials include nanoporous carbon and nanometal oxides, among which MOF-derived metal oxides are unique, porous and structured metal oxides prepared using MOF as a sacrificial template. MOF-derived oxides retain the overall morphology of the parent MOF, and organic matter acts as a "porogen" during the thermal decomposition process, regulating the morphological structure such as surface area and pores. The preparation of its derived metal oxides by the MOF sacrificial template method has great potential for enhancing phosphorus recovery. The Mg element has the advantages of low cost, low toxicity, small ionic radius, high charge density, and strong affinity with phosphorus. Therefore, this application uses the Mg-MOF sacrificial template method to prepare defect-rich nanomagnesium oxide, and calcination generates adsorption materials with different morphologies, pore structures, and defect concentrations (oxygen vacancies and magnesium defects) to achieve the purpose of efficient recovery of phosphate.

[0040] Example 1: The present invention discloses a method for preparing a double-defect Mg-MOF-derived metal oxide, comprising the following steps:

[0041] S1. 3 mmol DHTA (2,5-dihydroxyterephthalic acid) and 10 mmol MgNO3·6H2O were dissolved in 60 mL DMF (N`N-dimethylformamide), 4 mL EtOH (anhydrous ethanol) and deionized water, and ultrasonically treated for 2 h to form a mixed solution;

[0042] S2. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave with a volume of 100 mL, heated in an oven at 120 ° C for 24 h, and the crystals were collected after cooling; then washed twice with 50 mL of DMF and EtOH respectively, and dried in a vacuum oven at 80 ° C for 8 h for later use;

[0043] S3. The washed crystals are heated to 600° C. at a heating rate of 5° C. / min in a muffle furnace and calcined in an air atmosphere for 8 h to obtain the nano-metal oxide, which is recorded as DHTA-MgO.

[0044] Example 2: The present invention discloses a method for preparing a double-defect Mg-MOF-derived metal oxide, comprising the following steps:

[0045] S1. 3 mmol H3BTC (1,3,5-benzenetricarboxylic acid) and 10 mmol MgNO3·6H2O were dissolved in 60 mL DMF (N`N-dimethylformamide), 4 mL EtOH (anhydrous ethanol) and deionized water, and ultrasonically treated for 2 h to form a mixed solution;

[0046] S2. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave with a volume of 100 mL, heated in an oven at 120 ° C for 24 h, and the crystals were collected after cooling; then washed twice with 50 mL of DMF and EtOH respectively, and dried in a vacuum oven at 80 ° C for 8 h for later use;

[0047] S3. The washed crystals are heated to 600° C. at a heating rate of 5° C. / min in a muffle furnace and calcined in an air atmosphere for 8 h to obtain the nano metal oxide, which is recorded as H3BTC-MgO.

[0048] Example 3: The present invention discloses a method for preparing a double-defect Mg-MOF-derived metal oxide, comprising the following steps:

[0049] S1. 3 mmol AA (adipic acid) and 10 mmol MgNO3·6H2O were dissolved in 60 mL DMF (N`N-dimethylformamide), 4 mL EtOH (anhydrous ethanol) and deionized water, and ultrasonically treated for 2 h to form a mixed solution;

[0050] S2. The mixed solution was transferred to a polytetrafluoroethylene-lined autoclave with a volume of 100 mL, heated in an oven at 120 ° C for 24 h, and the crystals were collected after cooling; then washed twice with 50 mL of DMF and EtOH respectively, and dried in a vacuum oven at 80 ° C for 8 h for later use;

[0051] S3. The washed crystals are heated to 600° C. at a heating rate of 5° C. / min in a muffle furnace and calcined in an air atmosphere for 8 h to obtain the nano-metal oxide, which is recorded as AA-MgO.

[0052] like Figure 1As shown in the SEM and TEM spectra, the three materials are all disorderly arranged in the form of regular octahedral nanoparticles with a particle size of about 50 nm, but the structures formed are obviously different. DHTA-MgO and H3BTC-MgO are assembled by agglomeration of smaller nano-octahedral particles, and there are large circular holes on the surface of the materials (such as Figure 1 As can be seen in b and f in the figure), AA-MgO has narrow and elongated holes (such as Figure 1 The TEM lattice images show that the crystal surfaces of the three materials all contain defects (such as Figure 1 The lattice widths of the 111 and 200 planes of the three materials are measured and calculated to be 0.243 nm and 0.211 nm, respectively, which are consistent with the lattice widths of MgO (PDF#00-004-0829). The specific surface area, pore size and pore volume of the material will affect the adsorption performance. The physical properties of DHTA-MgO, H3BTC-MgO and AA-MgO are shown in Figure 2 The nano-metal oxides prepared by AA also formed slit-shaped elongated pores. AA-MgO had the largest specific surface area. H3BTC-MgO and AA-MgO had larger average pore size and pore volume than DHTA-MgO.

[0053] The element states of DHTA-MgO, H3BTC-MgO and AA-MgO materials are shown in Figure 3-5 The full spectra of the three materials confirmed the presence of O and Mg, proving once again that the Mg-MOF precursor generates MgO after calcination. The O 1s fine spectrum shows that the oxygen element of the three materials is in the form of adsorbed oxygen (O ads ), hydroxyl oxygen (O -OH ) and lattice oxygen (O lat ) exists, according to O ads / O lat The values ​​determined that the concentration of oxygen vacancies in the materials showed a trend of AA-MgO>H3BTC-MgO>DHTA-MgO. The sacrificial template method with MOF as the precursor can prepare MgO rich in oxygen vacancies because the pyrolysis of the MOF precursor causes the O to vibrate and escape, forming oxygen vacancies. The Mg 1s fine spectrum shows that compared with DHTA-MgO, the MgO peak of H3BTC-MgO and AA-MgO shifts toward the direction of high binding energy, the electron cloud density decreases, and charge transfer occurs. The defect types and concentrations detected by EPR are shown in Figure 6 All three materials show signals at g=2.003, among which AA-MgO has the strongest signal, indicating that all materials have produced oxygen defects, and AA-MgO has the highest oxygen defect concentration. All three materials show signals at g=1.981, and H3BTC-MgO has the strongest signal, indicating that all three materials have produced magnesium vacancies.

[0054] The adsorption isotherm model was fitted by the Langmuir and Freundlich models ( Figure 7 The fitting parameters are shown in Figure 8 It can be seen that the Langmuir isotherm model fits nano-magnesium oxide better. Among them, AA-MgO shows better adsorption performance, and the adsorption amount is 4.04 and 1.09 times that of DHTA-MgO and H3BTC-MgO, respectively. Pseudo-first-order kinetics and pseudo-second-order kinetics are used to fit the adsorption kinetics of the material ( Figure 7 b and Fig. 9 The fitting results show that the R values ​​of the two models for the three materials are 2 The difference is not big, among which the q obtained by pseudo-second-order kinetic fitting is e It is closer to the actual experimental results, indicating that the adsorption of phosphate by these three materials includes physical adsorption and chemical adsorption, with chemical adsorption being the main one.

[0055] Example 4: The present application also discloses a use of a double-defect Mg-MOF-derived metal oxide. Based on the above-mentioned method for preparing a double-defect Mg-MOF-derived metal oxide, the nano metal oxide has both oxygen defects and magnesium defects, and is used to adsorb and remove phosphates from wastewater. Preferably, the nano metal oxide prepared by AA has oxygen defects and magnesium defects, and also forms slit-shaped elongated holes to expose more binding sites for adsorbing and removing phosphates from wastewater. At the same time, the nano metal oxide prepared by AA has an adsorption capacity of more than 300 mg P / g of phosphate in wastewater under an environment of pH = 8. In addition, when applied to aquaculture wastewater with a concentration of 40 mg P / L, the phosphate removal rate of the nano metal oxide prepared by AA is 100% after the dosage is increased to 1.2 g / L.

[0056] Solution pH is an important parameter that determines the phosphate adsorption capacity. The effect of solution pH on the phosphate adsorption performance of nano-magnesium oxide is as follows: Figure 7 As shown in c, within the pH range studied, the adsorption of DHTA-MgO and H3BTC-MgO increased by 179.14 mg P / g and 159.87 mg P / g, respectively, within the pH range of 4-12. This phenomenon is caused by the change of the surface material of the material. As the pH increases, the surface of MgO is hydrated and dissolved to generate Mg(OH) + , Mg(OH) + After formation, Mg is released 2+ and OH - , it is easier to form supersaturated Mg at the vacancy 2+The adsorption capacity of AA-MgO increased when the pH value was 8, reaching the highest adsorption capacity of 323.15 mg P / g, which was 3.88 and 1.48 times that of DHTA-MgO and H3BTC-MgO. pzc is 8.57 (e.g. Figure 7 As shown in d in the figure, when pH < 8.57, i.e. pH = 8, the material surface is positively charged, and electrostatic attraction occurs with phosphate anions, resulting in the maximum phosphate adsorption. When pH > 8.57, the material surface is negatively charged, and electrostatic repulsion occurs with phosphate anions, resulting in a decrease in phosphate adsorption. The final pH of the phosphate solution with the addition of the three materials is 8-11, so it can be used to improve the pH of acidic water.

[0057] Keeping other experimental conditions unchanged, 0.1-2 g / L AA-MgO was added to 160 mg P / L simulated phosphate wastewater at pH = 8 (e.g. Figure 7 As shown in point e in the figure, it is calculated that when the adsorbent is added at a dosage of more than 0.8 g / L, the phosphate removal rate reaches 100%, but the adsorption amount decreases; when the dosage is 0.2 g / L, the adsorbent has the largest adsorption amount of phosphate. At this dosage, the material's performance in recovering phosphorus in wastewater is maximized, ensuring the phosphorus removal effect while avoiding material waste.

[0058] In actual water bodies, other coexisting substances besides phosphates will compete with phosphate for active sites and reduce the adsorption effect of phosphate. In the laboratory simulation of phosphate wastewater, different anions and cations as well as humic acid (HA) (such as Figure 7 The effect of coexisting substances on the phosphate adsorption performance of AA-MgO was studied. - 、NO3 - 、SO4 2- 、HCO3 - , K + 、Na + NH4 + and Ca 2+ It has a slight effect on the material's ability to adsorb phosphate, but with the increase of HA concentration, the inhibitory effect on the material's adsorption of phosphate becomes more and more significant, and when the concentration reaches 70 mg / L, it decreases by 29.1% compared with the blank control. Therefore, when treating phosphorus-containing wastewater, it is necessary to avoid or reduce the presence of humic acid components in the wastewater. The reason is that HA binds to the material surface through chelation, affecting the adsorption of phosphate. At the same time, HA competes with phosphate for binding sites, resulting in a decrease in phosphorus adsorption.

[0059] The adsorbent performance was verified in actual aquaculture wastewater, and the phosphorus removal effect of different dosages of AA-MgO in different actual wastewaters was explored (such as Figure 7As shown in h in the figure). The initial pH of the aquaculture wastewater is 7.83±0.02, and the concentration is 38.39±0.2mg P / L. Due to the influence of coexisting substances in the water, the adsorption capacity of the material in the actual water body has decreased. When 0.2g / L is added to the aquaculture wastewater, the phosphate removal rate is 64%. When the addition amount is increased to 1.2g / L, the phosphate removal rate is 100%, and the phosphorus content of the water body is reduced to below the eutrophication standard of the water body (0.02mg P / L), achieving the purpose of recovering phosphorus from the wastewater.

[0060] like Fig.10 As shown in the figure, the surface morphology of the three materials changed significantly after the adsorption of phosphate. From the SEM image, it can be observed that the surface of DHTA-MgO becomes smoother after the adsorption of phosphate, because the phosphate fills the pores; the macropores of H3BTC-MgO are completely filled after the adsorption of phosphate, and the combined phosphate forms flaky crystals wrapped on the surface of the material; the slits of AA-MgO are also filled with phosphate flaky crystals after the adsorption of phosphate, and the combined phosphate forms flaky crystals wrapped on the surface of the material.

[0061] like Fig.11 As shown in the XPS full spectrum, the P 2p characteristic peak appeared after adsorption, indicating that the phosphate was successfully adsorbed. The fine spectrum of P 2p showed that the phosphate was in the form of HPO4 2- (133.68eV) and H2PO4 - (132.95eV) is adsorbed onto the surface of the material. After adsorption, the Mg 1s peak area is significantly reduced, indicating that Mg combines with phosphate as an adsorption site to form a magnesium-phosphorus compound. The characteristic peak moves slightly toward the high binding energy direction, and the Mg electron cloud density decreases, indicating that the valence band electrons of Mg 1s have been transferred to phosphate. After adsorption, the oxygen vacancy concentration of the material decreases by 2.60 times compared with that before adsorption, indicating that the oxygen vacancies are consumed as phosphate adsorption sites, and the phosphate preferentially bonds with the electrons provided by the adsorbed oxygen.

[0062] DFT calculations were used to optimize the adsorption model of phosphate on the adsorption crystal plane (111) under perfect conditions, oxygen vacancies, and magnesium vacancies, and to calculate the vacancy formation energy and adsorption energy, as well as the spin polarization density of states (DOS) before and after the adsorption of phosphate. Fig.12 It can be seen from the DFT calculation results that magnesium defects (V Mg )'s formation energy E f = 0.108eV less than oxygen vacancy (V O )'s formation energy E f =4.11eV, indicating that V Mg The formation of V O More favorable, and in V Mg After formation, the surface structure of the material was deformed, indicating that V MgThe formation of V is beneficial to structural stability. Especially after adsorption of phosphate, Mg The more negative the adsorption energy, the more positive the adsorption of HPO4 2- The stronger the adsorption. O The surface structure of HPO4 2- The strongest adsorption is on the surface of MgO, followed by the perfect MgO surface, and the weakest adsorption is on the surface of V Mg At the same time, it can be seen from the DFT calculation results that the adsorption site in perfect AA-MgO is metallic magnesium. In order to further understand HPO4 2- The adsorption pattern on the AA-MgO surface was analyzed by density of states (DOS). Fig.12 As shown in b, d, and f in the figure), for all three model surfaces, the O 2p orbital contributes mainly to the valence band, and the hybridization of the O 2p orbital and the Mg 1s orbital and 2p orbital contributes to the conduction band. Therefore, DFT calculations further confirm that the order of phosphate adsorption on AA-MgO is V O >Magnesium Metal>V Mg , and the adsorption mechanism of phosphate is ligand exchange, intrasphere complexation and electrostatic attraction.

[0063] like Fig.13 As shown in the figure, the main adsorption sites of phosphate adsorption by AAMgO are oxygen vacancies, metallic magnesium and magnesium vacancies. The phosphorus removal mechanism of AAMgO involves electrostatic attraction, intrasphere complexation and ligand exchange. The adsorption mechanism mainly consists of three points: (1) When the pH is less than the zero potential, electrostatic adsorption allows phosphate ions to contact the surface of the material; (2) Nano-magnesium oxide and phosphate ions undergo inner-sphere complexation to form magnesium hydrogen phosphate; (3) The hydroxyl groups on the surface of the material are removed by ligand exchange, allowing the phosphate ions to bind tightly.

[0064] The present invention adopts Mg-MOF sacrificial template method to calcine and generate nano magnesium oxide with different morphology, pore structure and defect concentration, and has high concentration of oxygen defect and magnesium defect at the same time. In particular, the nano metal oxide prepared by AA also forms slit-type elongated holes to expose more binding sites, and adsorbs and removes phosphate in wastewater through the adsorption mechanism of ligand exchange, intra-sphere complexation and electrostatic attraction, so as to achieve the purpose of efficient recovery of phosphate. At the same time, the defect-rich nano magnesium oxide is prepared by Mg-MOF sacrificial template method, and the adsorption amount of phosphate in wastewater can be greater than 300mg P / g, which is much higher than the adsorption capacity of phosphate by phosphorus adsorption materials such as biochar, LDH and perovskite (the adsorption capacity is generally 50-200mg P / g). In addition, in actual aquaculture wastewater, when the AA-MgO dosage is 1.2g / L, the phosphate removal rate reaches 100%, indicating that it has the potential for practical application and has a high application and promotion value.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a double-defect Mg-MOF-derived metal oxide, characterized in that: The steps include: S1. Dissolving DHTA, H3BTC or AA and a magnesium metal salt in DMF, EtOH and deionized water to form a mixed solution, wherein the magnesium metal salt is MgNO3·6H2O or MgCl3·H2O; S2. The mixed solution is treated at high temperature and the crystals are collected and washed for later use; S3. calcining the washed crystals at high temperature to obtain nano metal oxides.

2. The method for preparing a double-defect Mg-MOF-derived metal oxide according to claim 1, characterized in that: In step S1, DHTA, H3BTC or AA and MgNO3·6H2O in a ratio of 1:3-1:4 were dissolved in 60 mL DMF, 4 mL EtOH and 4 mL deionized water, and ultrasonically treated for 1-2 h to form a mixed solution.

3. The method for preparing a double-defect Mg-MOF-derived metal oxide according to claim 1, characterized in that: Step S2 includes: The mixed solution is heated in an oven at 120-180° C. for 12-48 hours, and the crystals are collected after cooling overnight; The product was washed twice with 50 mL of DMF and EtOH respectively, and dried at 80° C. for 8 h.

4. The method for preparing a double-defect Mg-MOF-derived metal oxide according to any one of claims 1 to 3, characterized in that: In step S3, the washed crystals are calcined at 600° C. in an air atmosphere for 8 hours to obtain the nano metal oxide.

5. The method for preparing a double-defect Mg-MOF-derived metal oxide according to claim 1, characterized in that: In step S1, AA and MgNO3·6H2O are dissolved in DMF, EtOH and deionized water to form a mixed solution.

6. A use of a double-defect Mg-MOF derived metal oxide, based on the preparation method of a double-defect Mg-MOF derived metal oxide according to claim 1, characterized in that: The nano metal oxide has both oxygen defects and magnesium defects and is used for adsorbing and removing phosphate in wastewater.

7. The use of a double-defect Mg-MOF derived metal oxide according to claim 6, characterized in that: The nano metal oxide prepared by using AA has oxygen defects and magnesium defects, and also forms slit-shaped elongated holes to expose more binding sites for adsorbing and removing phosphate in wastewater.

8. The use of a double-defect Mg-MOF derived metal oxide according to claim 7, characterized in that: The nano metal oxide prepared by using AA has an adsorption capacity of more than 300 mg P / g for phosphate in wastewater under the environment of pH=8.

9. The use of a double-defect Mg-MOF derived metal oxide according to claim 8, characterized in that: The nano metal oxide prepared by AA is applied to aquaculture wastewater with a concentration of 40 mg P / L, and the phosphate removal rate after adsorption equilibrium at a dosage of 1.2 g / L is 100%.